Key players inducing skin diseases and skin aging and potential preventive or therapeutic strategies using phytochemicals - Hamid Mostafavi Abdolmaleky; Jinrong Zhou (Journal of Dermatologic Science and Cosmetic Technology, 2025)
Skin, the largest organ in the human body, consists of three distinct layers and is a barrier against hazardous environmental exposures to safeguard overall body health. While the superficial layers of skin and their appendages, like hair, are constantly diminished, skin stem cells continuously regenerate new hair and skin cells to replace them. As we age, the regenerative capacity of skin stem cells is reduced, and skin wound healing and hair generation efficiency is compromised. At the same time, the production of collagen that supports the skin's structure, elasticity, texture, and appearance is reduced, leading to signs of skin aging such as wrinkles, sagging, and loss of skin firmness, which make skin vulnerable to hazardous environmental perturbations. In addition to a sophisticated local neuroendocrine system, several genes such as SOX9, NOTCH, TGFBs, CTGF, AGR3, DSTYK, TPCN2, and collagen, play vital roles in skin integrity and health. Environmental factors such as contaminants, toxins, sun or UV radiation, infections, and skin microbiome dysbiosis negatively impact skin health, primarily by affecting skin stem cells and/or critical genes supporting skin health. Conversely, various nutritional elements, phytochemicals (e.g., curcumin, quercetin, rosemary, phenolic acids, and sesamin), as well as skin and gut microbiome parameters, help support skin health and prevent skin diseases or premature skin aging. This narrative review explores these topics and introduces potential remedies to promote skin health and mitigate skin aging and diseases.